Comprehensive plasma profiling for the characterization of graft-versus-host disease biomarkers - De Bock, Muriel; Beguin, Yves; Leprince, Pierre; Willems, Evelyne; Baron, Frédéric; Deroyer, Céline; Seidel, Laurence; Cavalier, Etienne; de Seny, Dominique; Malaise, Michel; Gothot, André; Merville, Marie-Paule; et al. (Talanta, 2014)
Acute graft-versus-host disease (aGVHD) remains a life-threatening complication of hematopoietic stem cell transplantation (HSCT), limiting its application. To optimize management of aGVHD and reduce therapy-related toxicity, early specific markers are needed. The main objective of this study was thus to uncover diagnostic biomarkers comparing plasma protein profiles of patients at the time of acute GVHD diagnosis and of patients undergoing HSCT without aGVHD. Additional analysis of samples taken 15 days before aGVHD diagnosis was also performed to evaluate the potential of the newly discovered biomarkers for early diagnosis. To extract a maximum of information from plasma samples, we used three complementary proteomic approaches, namely 2D-DIGE, SELDI-TOF-MS and 2D-LC-MSE. We identified and confirmed by means of a independent techniques, the differential expression of several proteins indicating significantly increased inflammation response and disturbance in the coagulation cascade. The variation of these proteins was already observed 15 days before GVHD diagnosis, suggesting the potential early detection of the disease before symptoms appearance. Finally, logistic regression analysis determines a composite biomarker panel comprising fibrinogen, fragment of fibrinogen beta chain, SAA, prothrombin fragments, apolipoprotein A1 and hepcidin that optimally discriminated patients with and without GVHD. The area under the receiver operating characteristic curve distinguishing these 2 groups was 0.95. ; Peer reviewed